Neoliberalisation of the Kgalagadi Transfrontier Park as a tourist region - Rattle, Jessica Mary (Department of Environmental and Geographical Science, 2015)
Proponents of transfrontier conservation areas (TFCAs) make a number of claims in favour of this relatively new conservation strategy, one of which is that it leads to an increase in tourism. Despite the growing body of literature on the subject of TFCAs, very little research has been conducted on whether or not this assumption is true. This study therefore draws on and situates itself within this literature on TFCAs and the neoliberalisation of nature and seeks to test this claim through the use of the Kgalagadi Transfrontier Park (KTP) as a case study. This is achieved firstly by assessing the changes in tourism development that have taken place both within the Park and in the area surrounding it as a result of the KTP's formation, and secondly by comparing the KTP's tourist levels prior to becoming a TFCA with those from after the TFCA was established, in order to determine what trends and changes have taken place as a result of this development. In doing so, this paper challenges the claim that TFCAs automatically lead to an increase in tourism and tourist development by showing that the link between the two is tenuous at best. It also broadens the scope of enquiry on the subject of TFCAs by analysing the relationship between TFCAs and the small scale, nature-based economic activities that take place around them, a matter which is largely ignored in the literature and, in doing so, critiques the assumption that all nature-based economic activities are part of a wider neoliberal agenda.